Relationship between stunting and clinical ear, nose and throat disorders - Aryo Mandraguna Wibowo; Arif Dermawan; Ratna Anggraeni (PERHATI-KL, 2022)
ABSTRACTBackground: Stunting is an impediment marker for child welfare. Based on the United Nations Nutrition report, in 2018, as many as 50.5 million children worldwide under the age of 5 years were wasting and 150.8 million were stunting. Stunting is associated with morbidity, mortality, stunted-child- development, decreased learning capacity, increased risk of infection, and decreased productivity. Until now, stunting is still a problem in many countries, including Indonesia which calls for serious solution. Stunting is associated with deficiencies of micronutrients such as vitamins A, D, zinc and iron resulting in impaired physical development and decreased immune system. In the field of ORL-HNS, stunting in toddlers could cause various disorders such as impaired hearing development, otitis media, rhinitis, and tonsillitis. Purpose: To describe the relationship between stunting and clinical abnormalities occurrence in the ORL-HNS, to increase awareness of stunting prevention and the related ORL-HNS disorders, and to be a reference for further research of ORL-HNS disorders in stunting patients. Literature review: Stunting or failure to thrive is a condition that describes a chronic undernutrition status during a child’s growth and development since the beginning of life, which is represented by a z-score of height for age less than minus two standard deviations based on the WHO growth standard curve. Conclusion: Stunting is a condition caused by an unbalanced nutritional intake during the golden period, not by growth hormone abnormalities, nor by certain diseases. Micronutrient deficiency could have a role in the occurrence of several clinical abnormalities of ORL-HNS in stunting children.ABSTRAKLatar belakang: Stunting merupakan penanda untuk kesejahteraan anak. Berdasarkan laporan United Nations Nutrition pada tahun 2018 sebanyak 50,5 juta anak di seluruh dunia yang berusia di bawah 5 tahun mengalami wasting dan sebanyak 150,8 juta mengalami stunting. Stunting berhubungan dengan morbiditas, mortalitas, terhambatnya perkembangan anak, penurunan kapasitas belajar, peningkatan risiko infeksi, dan penurunan produktivitas. Hingga saat ini, stunting masih menjadi salah satu permasalahan yang perlu diperhatikan di banyak negara, termasuk di Indonesia. Stunting berhubungan dengan defisiensi mikronutrien seperti vitamin A, D, zink dan zat besi yang berakibat terganggunya perkembangan fisik dan penurunan sistem imunitas. Di bidang THT-KL, stunting pada balita diduga dapat menimbulkan berbagai kelainan seperti gangguan perkembangan pendengaran, otitis media, rinitis, dan tonsilitis. Tujuan: Untuk menggambarkan adanya hubungan stunting dengan terjadinya kelainan klinis di bidang THT–KL, meningkatkan kewaspadaan untuk mencegah stunting dan kelainan THT-KL yang berhubungan dengan stunting, serta dapat menjadi rujukan penelitian lebih lanjut mengenai prevalensi gangguan THT-KL pada pasien dengan stunting. Tinjauan pustaka: Stunting atau gagal tumbuh adalah suatu kondisi yang menggambarkan status gizi kurang yang memiliki sifat kronis pada masa pertumbuhan dan perkembangan anak sejak awal masa kehidupan yang dipresentasikan dengan nilai z-score tinggi badan menurut umur kurang dari minus dua standar deviasi berdasarkan kurva standar pertumbuhan WHO. Kesimpulan: Stunting merupakan kondisi yang disebabkan oleh kurang seimbangnya asupan gizi pada masa periode emas, bukan disebabkan oleh kelainan hormon pertumbuhan maupun akibat dari penyakit tertentu. Hasil dari beberapa penelitian mengungkapkan bahwa defisiensi mikronutrien dapat berperan terhadap terjadinya beberapa kelainan klinis THT–KL pada anak dengan stunting.